Simultaneous Determination of Content of Ten Heavy Metals in Detergents from China by ICP-MS - HONGXING, ZHANG; FANG, XU; YU-KUI, RUI (Asian Journal of Chemistry, 2010)
The safety of detergents is attracting increasing attention. The content of heavy metals in four primary brand detergents from the Beijing market were analyzed by ICP-MS. The results show that the heavy metal content of detergents is high, with the Ti content being higher than the other heavy metals. However, heavy metal content varied significantly from brand to brand. The data suggest that consumers should decrease the use of detergents and select brands containing less heavy metal if they must be used. The department with responsibility for the hygiene of detergents should investigate all detergent products to ensure the safety of consumers.